One year patient follow-up results after endovascular abdominal aortic aneurysm repair at University Medical Centre Ljubljana - Bregar, Urška (Medicinski razgledi (Supplement), 2024)
BACKGROUNDS. Endovascular abdominal aortic aneurysm repair (EVAR) is commonly used to treat abdominal aortic aneurysms (AAA). In our department, the outcomes following EVAR after 30 days, one year and later have been monitored systematically in all patients since 2023. METHODS. All the patients after EVAR, which were hospitalized at our department from January 2023 until May 2024, have been included in our analysis. Our aim is to follow the outcomes in patients after EVAR during hospitalization, after 30 days, one year and later. RESULTS. This analysis included 107 patients after EVAR (elective and urgent) since the first of January 2023, of these 87 were men and 20 were women (mean age 74.4 ± 5.2). The mean AAA diameter was 58 ± 7 mm. We analysed the duration of hospitalization in elective and urgent patients (5.6 ± 2.9 days and 16.2 ± 8.2 days, respectively). 50% of patients after EVAR had a haematoma on the puncture site. 69 patients already had CT angiography after EVAR by the end of April 2024; there were 23 endoleaks detected (type 2 in 21 patients, type 1 in one patient and type 3 in one patient). DISCUSSION. Since January 2023 and up until now, 107 patients have been treated with EVAR at our centre. The presence of endoleaks type 1, 2 and 3 and other complications are comparable with the data from other registries.
Keywords: anevrizma trebušna aorta; angiografija; endovaskularna sanacija anevrizme trebušne aorte; EVAR; hematom; žilna kirurgija